Devotional Hindu Dance: A Return to the Sacred - MisirHiralall, Sabrina D. (Springer eBook Collection, 2021)
Chapter 1: Introduction -- Chapter 2: An Overview of the History of Hindu Dance Education -- Chapter 3: Defining Devotional Hindu Dance -- Chapter 4: Beginning to Engage in Devotional Hindu Dance -- Chapter 5: Developing Devotional Hindu Dance Choreography -- Chapter 6: Conclusion.